1991
DOI: 10.1016/0304-3959(91)90205-c
|View full text |Cite
|
Sign up to set email alerts
|

The validity of the General Health Questionnaire for first-stage screening for mental illness in pain clinic patients

Abstract: The validity of the 28-item version of the General Health Questionnaire (GHQ-28) was determined by comparison with the Clinical Interview Schedule (CIS) in 56 pain clinic patients. Despite some limitations, the GHQ can be used effectively and cheaply as the first stage of an assessment to identify potential "cases" of mental disorder which must then be verified using a second-stage clinical interview such as the CIS. This process can result in a considerable reduction in the proportion of patients requiring a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In the present study, two self‐rating psychological questionnaires were incorporated. GHQ and POMS have been used to screen the existence of mental disorders and to evaluate the treatment outcome in studies of chronic pain (22–25). More importantly, a previous study revealed that these two psychological questionnaires reported to be useful screening tools for detecting mental disorders in dental patients with occlusion‐related problems (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, two self‐rating psychological questionnaires were incorporated. GHQ and POMS have been used to screen the existence of mental disorders and to evaluate the treatment outcome in studies of chronic pain (22–25). More importantly, a previous study revealed that these two psychological questionnaires reported to be useful screening tools for detecting mental disorders in dental patients with occlusion‐related problems (4).…”
Section: Discussionmentioning
confidence: 99%
“…ª 2012 Blackwell Publishing Ltd disorders and to evaluate the treatment outcome in studies of chronic pain (22)(23)(24)(25). More importantly, a previous study revealed that these two psychological questionnaires reported to be useful screening tools for detecting mental disorders in dental patients with occlusion-related problems (4).…”
Section: B I O -P S Y C H O -S O C I a L A S P E C T S O F O C C L U mentioning
confidence: 99%
“…Although GHQ is not a diagnostic instrument, it can be used in the first stage to identify potential cases of depression, which must in turn be confirmed using clinical assessment [30]. This cross-sectional study reports on the impact of MSD on mental health as measured by a screening scale.…”
Section: Discussionmentioning
confidence: 99%
“…Patients choose one of five response alternatives from 'not at all' to 'much mote than usual' (scored 0-4) to describe how much of the relevant item they have experienced in the past few weeks. It had high sensitivity (true positive rate) and good specificity (true negative rate) when tested against the Clinical Interview Schedule (Benjamin, Lennon & Gardner, 1991;Goldberg. Cooper, Eastwood.…”
Section: Methodsmentioning
confidence: 99%